2017
DOI: 10.1016/j.bbrc.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

STAP-2 interacts with Pyk2 and enhances Pyk2 activity in T-cells

Abstract: STAP-2 is an adaptor molecule regulating several signaling pathways, including TLRs and cytokine/chemokine receptors in immune cells. We previously reported that STAP-2 enhances SDF-1α-induced Vav1/Rac1-mediated T-cell chemotaxis. However, the detailed mechanisms of STAP-2 involvement in enhancing T-cell chemotaxis remain unknown. In the present study, we demonstrate that STAP-2 directly interacts with Pyk2, which is a key molecule in the regulation of SDF-1α/CXCR4-mediated T-cell chemotaxis, and increases pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…STAP-2 contains four putative tyrosine phosphorylation sites at residues 22, 250, 310, and 322, and phosphorylation of Tyr250 plays an important role in some STAP-2 functions (11,25). To evaluate the effects of LCK on STAP-2 phosphorylation, we analyzed a series of STAP-2 YF mutants, in which each tyrosine residue of STAP-2 was individually substituted with a phenylalanine residue, in LCK-transfected 293T cells (Fig.…”
Section: Phosphorylation Of Stap-2 At Tyr250 By Lck Is Required To Re...mentioning
confidence: 99%
“…STAP-2 contains four putative tyrosine phosphorylation sites at residues 22, 250, 310, and 322, and phosphorylation of Tyr250 plays an important role in some STAP-2 functions (11,25). To evaluate the effects of LCK on STAP-2 phosphorylation, we analyzed a series of STAP-2 YF mutants, in which each tyrosine residue of STAP-2 was individually substituted with a phenylalanine residue, in LCK-transfected 293T cells (Fig.…”
Section: Phosphorylation Of Stap-2 At Tyr250 By Lck Is Required To Re...mentioning
confidence: 99%
“…STAP-2 deficiency results in the reduction of SDF-1α-induced T cell migration, whereas Jurkat cells overexpressing STAP-2 show increased cell migration toward SDF-1α [ 34 ]. Mechanical studies have suggested that STAP-2 affects the activity of Rho GTPases, such as RhoA, Rac1, and Cdc42, with its ability to function as a scaffold protein between Vav1 and Pyk2 to initiate Pyk2-mediated Vav1 phosphorylation in T cells [ 34 , 35 ]. STAP-2 Y250 phosphorylation is also an important step for the successful function of an adaptor protein between these molecular types of machinery [ 35 ].…”
Section: Functional Role Of Stap-2 In T Cellsmentioning
confidence: 99%
“…The other possible involvement of STAP-2 in SDF-1α-mediated signals is the regulation of Pyk2, which forms signaling complexes with paxillin, the CT10 regulator of kinase (Crk), and p130 Crkassociated substrate (Cas). 32) STAP-2 directly interacts with Pyk2 and upregulates Pyk2 phosphorylation. Pyk2 itself can induce STAP-2 Tyr250 phosphorylation, which is critical for maximal interactions between STAP-2 and Pyk2 33) (Fig.…”
Section: Effects Of Stap-2 On T Cell Migrationmentioning
confidence: 99%